Total Sky Imager observations and continuous radiation measurements during POLARSTERN cruise ANT-XXVIII/1 with links to images - Ronny Engelmann; Thomas Kanitz; Marlen Brückner; Henry Kleta; Andreas Macke (PANGAEA, 2014)
This data collection contains total Sky Imager observations and continuous radiation measurements during POLARSTERN cruise ANT-XXVIII/1 in 2011.